Physics Comprehensive and Contextual Teaching Material (PhysCCTM) untuk Meningkatkan Higher Order Thinking Skill (HOTS) Siswa SMA - Nugroho Prasetya Adi; Suparno Suparno; Mudilarto Mudilarto; Edi Istiyono; Rattiwizal Alpin Y; Muhammad Zaini; Syayid Qosim M.J.A (Universitas Sebelas Maret, 2017)
Abstract: This study aimed to: (1) produce Physics Comprehensive and Contextual Teaching Material (PhysCCTM) which was reasonably for physics learning in SMA, and (2) examine the effectiveness of Physics Comprehensive and Contextual Teaching Material (PhysCCTM) to increase students Higher Order Thinking Skill (HOTS). This research used R&D methods with 4D models consisting of (1) Define, (2) Design, (3) Developt, and (4) Disseminate. The resulted product is PhysCCTM. The data were colleted by using an evaluation sheet of product, and test of HOTS. The data were analyzed using Aiken V to assess the product quality, and N-Gain analysis. The result of this research produced teaching material PhysCCTM which: (1) was reasonably to increase students HOTS with very good category based on expert, teachers, and good category based the response of students, and (2) effective to increase students HOTS significantly by effectivity on Partial Eta Squared in Multivariate Test with the value is 90,4%. Abstrak: Penelitian ini bertujuan: (1) untuk menghasilkan Physics Comprehensive and Contextual Teaching Material (PhysCCTM) yang layak untuk pembelajaran fisika di SMA, dan (2) menguji efektivitas Physics Comprehensive and Contextual Teaching Material (PhysCCTM) dalam meningkatkan Higher Order Thingking Skill (HOTS) siswa SMA. Penelitian pengembangan ini menggunakan metode R&D dengan model 4D yang meliputi tahap (1) Define, (2) Design, (3) Develop, dan (4) Disseminate. Produk yang dihasilkan adalah PhysCCTM. Instrumen pengumpulan data yang digunakan adalah lembar penilaian perangkat pembelajaran, dan lembar penilaian HOTS. Teknik analisis data yang digunakan adalah Aiken V untuk melihat kualitas produk dan analisis General Linier Model (GLM). Hasil penelitian menunjukkan bahwa telah dihasilkan produk PhysCCTM yang: (1) layak digunakan untuk meningkatkan HOTS dengan kategori sangat baik berdasarkan penilaian ahli dan guru, serta kategori baik berdasarkan respon siswa, dan (2) efektif untuk meningkatkan HOTS siswa secara signifikan berdasarkan efektivitas pada Partial Eta Square di Multivariate Test dengan nilai 90,4%.